Patterns of Specialization and (Un)conditional Convergence: The Cases of Brazil, China and India - Hadengue, Marine; Warin, Thierry (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2014)
We propose to measure economic convergence for three emerging countries: Brazil/China/India. A first result is that the higher the level of productivity in an industry, the lower its growth rate, showing a convergence to the productivity frontier represented by the U.S. A first contribution is to propose a new definition of convergence, based on labor productivity vis-à-vis the technological frontier. A second contribution is that we use industry-level data to measure convergence. In doing so, we aim to reduce the biases of using trade data collected at the national level as in previous models.